Antibiotic Resistance and Probiotics: Knowledge Gaps, Market Overview and Preliminary Screening - Gordana Zavišić; Milka Popović; Svetlana Stojkov; Deana Medić; Vera Gusman; Nataša Jovanović Lješković; Aleksandra Jovanović Galović (MDPI AG, 2023)
Probiotics are among those products, the use of which is increasing, and they are available primarily as food/dietary supplements, as well as in the form of medicines. This study aims to assess the attitudes and practices of health professionals and students of health sciences, give a short overview of the probiotics currently on the market, and conduct a screening of five food supplements and one drug with respect to antibiotic resistance. Nearly half of the respondents in our survey state that probiotics have no side effects, while only 6.3% believe that the use of probiotics can lead to antibiotic resistance. In addition, more than 40% of the participants throw unused probiotics into municipal waste. The market analysis results indicate that probiotic products on the Serbian market have highly variable CFU counts, while the declared health claims cover numerous beneficial health effects, and they are sometimes even registered as medicines. Lactobacilli are frequently present in probiotic supplements, and are sold in pharmacies and online. The experimental results showed that antibiotic resistance is present in different types of lactobacilli in probiotic products. The risk of using probiotics, regardless of their beneficial health effects, should be taken into account in the future. An update to the regulations governing probiotics, including a stipulation for antimicrobial resistance (AMR) testing, should be established, and guidelines for their proper use and disposal put into place.